Minuman Khusus Ibu Hamil dan Ibu Menyusui: Pemenuhan terhadap Standar Nasional Indonesia dan Persepsi Konsumen - Ati Widya Perana; Nurheni Sri Palupi; Made Astawan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
There are 52 beverage products for pregnant and lactating women registered in 2007-2011. Conforming to the standard of this product is currently voluntary. However, considering the safety and public health concern, government may enforce this standard to be mandatory. The objectives of this study were: (a) to evaluate nutrient content declared on the label of registered beverage products for pregnant and lactating women compared with national standard, (b) to calculate the percentage of Recommended Dietary Allowance declared on the label compared to the nutrition need of pregnant and lactating women and (c) to analyze the consumer perception on the beverage products for pregnant (n=60) and lactating women (n=60). This study showed that 87% of beverage products for pregnant women and 59% of pro-ducts for lactating women did not meet the national standard. The compliance for nutrition ful llment in beverage products for pregnant and lactating women per serving based on RDA requirement was 1% to 62%. The survey showed that 43% of pregnant women and 48% of lactating women had important perception of these products. Pregnant women (32%) and lactating women (33%) choose nutrients as the first consideration when buying the products. 65% of pregnant women and 64% of lactating women consume these products through their own initiatives. 77% pregnant women and 54% lactating women state that the benefit of consuming these product is to ful ll the nutrients requirement.